2018
DOI: 10.1016/j.urology.2017.08.056
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Patient-specific Tumor Mold Using Magnetic Resonance Imaging and 3-Dimensional Printing Technology for Targeted Tissue Procurement and Radiomics Analysis of Renal Masses

Abstract: MRI-based preoperative 3D printing of tumor-specific molds allow for accurate sectioning of the tumor after surgical resection and colocalization of in vivo imaging features with tissue-based analysis in radiomics and radiogenomic studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 29 publications
(29 reference statements)
0
47
0
Order By: Relevance
“…This review shows that with use of low-cost materials or home-made 3D printers, the cost associated with 3D printed kidney models is less than USD$150, as shown in some studies (25,27,28,33). However, a high quality kidney model printed with flexible materials such as TangoPlus and with different colours to highlight renal tumours and vascular or renal collecting structures can cost up to USD$1,000 (15,16,18,26). Therefore, future research is needed to reduce the costs associated with 3D printed kidney models.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This review shows that with use of low-cost materials or home-made 3D printers, the cost associated with 3D printed kidney models is less than USD$150, as shown in some studies (25,27,28,33). However, a high quality kidney model printed with flexible materials such as TangoPlus and with different colours to highlight renal tumours and vascular or renal collecting structures can cost up to USD$1,000 (15,16,18,26). Therefore, future research is needed to reduce the costs associated with 3D printed kidney models.…”
Section: Discussionmentioning
confidence: 99%
“…There are 7 studies reporting the qualitative assessment of 3D printed models in renal disease (15,17,(25)(26)(27)(28)31). Three of them showed that patient's understanding of renal anatomy and pathology was improved with use of 3D printed models, with patient's satisfaction score more than 9 out of 10 (15,25,31).…”
Section: Qualitative Assessment Of 3d Printed Kidney Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Removing or trimming the fat may interfere with clinical practice, as it could compromise the surgical margins, which need to be evaluated for the presence of tumour cells 29 . A solution has been previously proposed for partial nephrectomy cases, using the inner parenchymal surface of the tumour as the base of the mould 25 . This method involved the surgeon inserting fiducial markers into the tumour during surgery, which interrupts the routine clinical pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the specimen is often covered by perinephric fat 23 , which further complicates the procedure and can make it impossible to identify relevant structures. Because of these restrictions, previous 3Dprinting-based co-registration methods for RCC have either been limited to pre-clinical models 24 , or have only focused on early-stage partial nephrectomy cases 25 , where the fat-free resection margin can be used as a base. In addition, none of the preivous methods addressed the issue of having di↵erent sectioning and imaging planes.…”
Section: Introductionmentioning
confidence: 99%